How to improve retrieval effectiveness on the web - Ferreira, J.; da Silva, A. R.; Delgado, J. (Proceedings of the IADIS International Conference on e-Society, 2004)
We explore the question of combining link analysis, content analysis and classification-based techniques to improve retrieval performance on the Web. We show the potential of combination and that relatively simple implementation of combination does improve the retrieval performance.